The temptation of graves in Salafi Islam : iconoclasm, destruction and idolatry - Beránek, Ondřej, 1980-; Ťupek, Pavel, 1980- (Edinburgh University Press, 2018)
In various parts of the Islamic world over the past decades virulent attacks have targeted Islamic funeral and sacral architecture. Rather than being random acts of vandalism, these are associated with the idea of performing one's religious duty as attested to in the Salafi/Wahhabi tradition and texts. Graves, shrines and tombs are regarded by some Muslims as having the potential to tempt a believer to polytheism. Hence the duty to level the graves to the ground (taswiyat al-qubūr). In illuminating the ideology behind these acts, this book explains the current destruction of graves in the Islamic world and traces the ideological sources of iconoclasm in their historical perspective, from medieval theological and legal debates to contemporary Islamist movements including ISIS.